The relationship between vitamin D levels, comprehensive geriatric assessment and anthropometric measurements - Meryem Cakir; Yasemin Ozkaya; Nafiye Ebru Terzi; Olgu Aygun; Halime Seda Kucukerdem; Elif Saki (PLoS ONE, 2025)
Introduction It is well-established that vitamin D deficiency increases with age. This study aims to investigate the relationship between vitamin D levels, comprehensive geriatric assessment and anthropometric measurements in elderly individuals. Methods In this retrospective cross-sectional analytical study, data from patients aged 65–100 registered with İzmir City Hospital Home Care Services were analyzed. The patients’ vitamin D levels were compared with their sociodemographic and clinical data, anthropometric measurements (BMI, ABSI, body fat percentage), and geriatric assessment results (activities of daily living, nutrition, mental status, depression, frailty, and sarcopenia). Data were analyzed using SPSS 26.0 Statistics program. Results This retrospective cross-sectional study included 439 elderly individuals aged 65–100 years receiving home healthcare services. In univariate analysis, no significant associations were found between vitamin D and other variables, except for hypertension (p = 0.049). ABSI values were higher in individuals vitamin D level with severe deficient and deficient compared to other groups, while BMI levels were found to be higher in the vitamin D deficient group (p < 0.001, p < 0.001, respectively). Additionally, the severe deficiency group had a higher frequency of pressure ulcers and lower Barthel Index scores (p = 0.033, p = 0.026, respectively). Correlation analysis revealed a significant negative relationship between vitamin D levels and ABSI (r = −0.184, p < 0.05) and the presence of pressure ulcers (r = −0.113, p < 0.05). Regression analysis confirmed these negative associations with ABSI (β = −0.179, p < 0.05) and pressure ulcers (β = −0.113, p < 0.05). Hypertension and BMI lost their significance in correlation and regression analyses. Conclusion Lower vitamin D levels were associated with higher ABSI values and a greater frequency of pressure ulcers. ABSI may be useful in predicting vitamin D deficiency, and monitoring vitamin D levels in patients with pressure ulcers is recommended.